Medical data transformation using rewriting - Ashish, Naveen; Toga, Arthur W. (Frontiers in Neuroinformatics, 2015)
This paper presents an approach to and system for declaratively transforming medical subjects’ data into a common data model representation. Our work is part of the “GAAIN” project on Alzheimer’s disease data federation. We present a general purpose data transformation system that we have developed by leveraging the existing state-of-the-art in data integration and query rewriting. In this work we have further extended the current technology with new formalisms that facilitate expressing a broader range of data transformation tasks, plus new execution methodologies to ensure efficient data transformation for disease datasets.